Skills of Educational Designer: the speech of the practice and practice of speech - Mirian Maia Amaral; Lina Cardoso Nunes (Universidade Estadual Paulista Júlio de Mesquita Filho, 2008)
This paper analise the relation between the speech of the practice of instructional design and the practice of that speech of educational designer, with base on the results of research, held in the Program Online FGV the Getulio Vargas Foundation. The study aimed to identify the skills required by the FGV for the performance of educational designer in the exercise of its function. The methodology adopted consisted of bibliografhic research and field, and was applied forms, and semi-structured interviews conducted. Forms and interviews with educational designers were used to check and confirm all information collected. The emphasized competences were those linked to knowledge and skills, communication and interpersonal relationships, planning, organization and proactivity, behaviors, in addition to the ethical and political-social received more emphasis. Among them, the more weight was given to communication skills and behavior.